Characteristics of Tuberculous Spondylitis Patients at Dr. M. Djamil Padang Hospital 2018-2020 - Athiyyah, Salsa Naudzul; Sahputra, Roni Eka; Reza, Mohamad (Frontiers on Healthcare Research, 2024)
Background: Tuberculosis is an infectious disease caused by Mycobacterium tuberculosis which has long been known and still one of the top 10 causes of death in the world. Tuberculosis spondylitis is one of the most common extrapulmonary tuberculosis. This study aims to describe the characteristics of patients diagnosed with tuberculous spondylitis at RSUP Dr. M. Djamil Padang in 2018 – 2020. Methods: This study is an observational descriptive study with a retrospective approach using medical record data from patients diagnosed with tuberculosis spondylitis at RSUP Dr. M. Djamil Padang 2018 - 2020. The sampling method used total sampling technique. Results: The results of this study show that tuberculous spondylitis is mostly in the age group 17 – 25 years (25%), the ratio between male and female gender is 1:1, patients come from outside Padang (78.8%), occupation most were housewives (27.5%), and most had no family history of tuberculosis (80%). Local pain is the most common clinical manifestation experienced by as many as 70 people. The lesion location is most often in the thoracic region (45%). Conclusion: Tuberculous spondylitis is most common in the age group 17 – 25 years, comes from outside the field, is a housewife, and has no family history of tuberculosis. Men and women have the same number of cases. Local pain is the most common clinical manifestation and the thoracic lesion is the most frequently found location.